FIVE YEAR FOLLOW UP OF 100 HEROIN ADDICTS IN PESHAWAR - Mufti, Khalid A; Said, Samina; Farooq, Saeed; Haroon, Asad; Nazeer, Abida; Naeem, Sher; Hussain, Iqbal (Journal of Ayub Medical College Abbottabad, 2004)
Background: Drug addiction has increased rapidly during the last 2 decades in Pakistan, however little has been done to explore and evaluate different treatments which are available locally. This paper describes five years follow up of heroin addicts from Peshawar, Pakistan, after an extended period of in patient detoxification. Methods: This was a longitudinal cohort study of 100 clients who were followed up for 5 years. The main interventions included; an extended in patient detoxification for 30 days, Motivational Interview, and training in coping strategies. Patients participated in both in-patient, and then after discharge, community based group therapy, as well as indigenous self-help groups as an integral part of the treatment. A modified version of Addiction Severity Index (ASI) was used along with urine analysis, to assess substance misuse in clients. Improvement was defined as being drug and crime free and being in purposeful employment. Results: At the end of the study period, out of a total of 70 clients, 16(23%) had improved, 54(77%) had relapsed, while 04(5%) had dropped out of the programme. As far as abstinence from drugs and crimes was concerned, 28% were abstinent at the end of 5 years follow up. Conclusions: An integrated community based indigenous approach can had good effect on outcome of heroin addiction in a medium term follow up. Keywords: Heroin, Drug Addiction, Follow up, Addicts